2021
DOI: 10.3390/ma14102696
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of NiTi-Based Eutectic Shape Memory Alloy Produced via Selective Laser Melting In-Situ Alloying by Nb

Abstract: This paper presents the results of selective laser melting (SLM) process of a nitinol-based NiTiNb shape memory alloy. The eutectic alloy Ni45Ti45Nb10 with a shape memory effect was obtained by SLM in-situ alloying using a powder mixture of NiTi and Nb powder particles. Samples with a high relative density (>99%) were obtained using optimized process parameters. Microstructure, phase composition, tensile properties, as well as martensitic phase transformations temperatures of the produced alloy were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The mechanical performances are comparable to those of conventional casted NiTiNb alloys but lower than those in the wrought state (see details in figure S12 in supplement). To the best of authors' knowledge, the tensile ductility of 9.5% is superior to the LPBF-fabricated NiTiNb alloys reported so far [8,32,33,74]. The enhanced mechanical performances are mainly attributed to the transition of the NiTi/Nb eutectics from meshlike into the rod-like and sphere-like morphology (figure 2).…”
Section: Mechanical and Functional Propertiesmentioning
confidence: 86%
See 1 more Smart Citation
“…The mechanical performances are comparable to those of conventional casted NiTiNb alloys but lower than those in the wrought state (see details in figure S12 in supplement). To the best of authors' knowledge, the tensile ductility of 9.5% is superior to the LPBF-fabricated NiTiNb alloys reported so far [8,32,33,74]. The enhanced mechanical performances are mainly attributed to the transition of the NiTi/Nb eutectics from meshlike into the rod-like and sphere-like morphology (figure 2).…”
Section: Mechanical and Functional Propertiesmentioning
confidence: 86%
“…Ni 3 Ti, Ti 2 Ni) [25,28]. To avoid these issues, the ISA of ternary NiTi-X SMAs was mainly carried out via L-PBF using the pre-alloyed NiTi powders as the base materials and using the ternary element powders as additives, such as NiTi with HfH 2 [29], NiTi with Fe [30] and NiTi with Nb [8,[31][32][33]. This ensures the formation of the NiTi phase, and the ISA-ed NiTi-based SMAs exhibit typical PT behavior and stress-strain response [8,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The above research mainly explained the relationship between the process parameters and the microstructure and phase transformation of the prepared samples. Recently, Igor Polozov et al [33] explored the microstructure and phase transformation temperature of NiTiNb prepared by SLM, which provided a reference for us to prepare NiTiNb by LSF, they found that the microstructure of SLM-NiTiNb was composed of B2-NiTi matrix, fine NiTi+β-Nb eutectic phase and residual un-melted Nb particles, and the phase transformation hysteresis was increased by about 40 • C compared with the traditional cast NiTiNb alloy. Therefore, we can use the combination of process parameters for reference and expect the influence of LSF process parameters on NiTiNb microstructure and phase transformation to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Both alloys showed superior compressive properties compared to the conventional TiAl-alloy. The in situ synthesis approach is often used in additive manufacturing research as an economical method for evaluating microalloying on known compositions, and [ 10 ] presented a study of adding niobium to nitinol powder. Despite the incomplete melting of niobium particles, it was possible to achieve the formation of a dense material, with subsequent heat treatment at 900 °C with 2 h of dwell allowing increasing martensitic transformation hysteresis as compared to the alloy without Nb addition from 22 to 50 °C, while the A f temperature increased from −5 to 22 °C.…”
mentioning
confidence: 99%
“…Another promising area is the investigation of materials and processes for the additive manufacturing of functional materials. Shape memory materials are now being actively researched for production by additive manufacturing and expanding possibilities of their application by corrections of alloying systems [ 10 ]. Particularly relevant in the global trend towards green energy are materials used in electrical machine component production, such as electricity conductors, soft-magnetic alloys, piezoceramics, etc.…”
mentioning
confidence: 99%